When Science Meets Digital Branding - Kaiping Chen; Todd Newman; Yanxi Zhou (Journal of Quantitative Description: Digital Media)
The science media ecosystem continues to dramatically change with the proliferation of digital media channels and platforms. While there are many different types of digital media filling this void, the use of online videos, particularly on YouTube, has become one of the main sources for information, specifically for science and environmental issues. While most researchers examine the content of online science news and information, we show that digital trace data, including hyperlinks, “likes”, and comments that are unique to participatory online media, can reveal interesting patterns about how and why people communicate and engage with content as well as other community members. Using climate change as a case study, we demonstrate how researchers can harness hyperlinks to understand who produces controversial science news and information online, and the motivations underlying how content creators use of hyperlinks for science communication and public engagement. While many existing studies in science communication have focused on understanding the political dimension of online science news and information, our paper reveals that digital branding is a crucial part of science communication on video-based platforms such as YouTube and TikTok. We find that amateur content creators and new media outlets use hyperlinks to promote their channel and other social media presences to raise revenue. While self-promotion through citing links to one’s other social media platforms is associated with more views, linking to revenue raising websites is not associated with more views. We discuss the implications of these contexts for the online science news and information ecosystem.